Paleobotany : plants of the past, their evolution, paleoenvironment, and application in exploration of fossil fuels - Agashe, Shripad N. 4 0 16; 5 (Enfield, NH : Science Pub., 1997)
Text book in paleobotany with special reference to India.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Evolutuion -- Paleobotany.;Plants, Fossil;Fossil fuel.;Paleoecology. -- India; 20; 2